REPUTASI PERUSAHAAN SEBAGAI MEDIATOR: PERAN CORPORATE SOCIAL RESPONSIBILITY, KUALITAS AUDIT, DAN FINANCIAL DISTRESS DALAM AGRESIVITAS PAJAK : (STUDI PADA PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA PERIODE 2019-2024) - Annisa Nur Fahira; Cornelia Desiana Matani; Elia Madatu Tandililing (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study examines the effect of Corporate Social Responsibility (CSR), audit quality, and financial distress on tax aggressiveness,with corporate reputation as a mediating variable in energy sector companies listed on the Indonesia Stock Exchange during 2019-2024. This research uses a quantitative approach with secondary data and Partial Least Square (PLS) analysis. The sample consists of 34 companies selected through purposive sampling. The results show that financial distress has a positive and significant effect on tax aggressiveness, while CSR and audit quality have no significant effect. Corporate reputation neither affects tax aggressiveness nor mediates the relationships between variables. These findings indicate that tax aggressiveness is more driven by financial pressure than by reputational or governance factors. The study highlights that non-financial signals such as CSR do not always reflect actual tax compliance.